From Enforcement to Prevention: Reorienting the KPK’s Role in Indonesia Hajj Governance - Nazwa Aprilia Salsabila; Hilman Nur (Riset Anak Bangsa, 2026)
Corruption in Hajj governance has the potential to cause state financial losses and erode public trust in a religious service that should be administered transparently and accountably. This study analyzes corruption-prevention strategies in Hajj governance through the role of the Corruption Eradication Commission (KPK) in realizing good governance and examines the constraints encountered in their implementation following the revision of the KPK Law. The study employs normative legal research using statutory and conceptual approaches and a literature review of primary, secondary, and tertiary legal materials. The findings show that the KPK's role in Hajj governance is not limited to repressive functions through its authority to conduct inquiries, investigations, and prosecutions of corruption offenses; it also encompasses preventive measures through strengthened oversight, service digitalization, greater transparency in Hajj fund management, and inter-institutional coordination. These strategies are important instruments for advancing the principles of good governance, particularly transparency, accountability, effectiveness, and integrity in public service. However, implementation continues to face bureaucratic complexity, weak institutional coordination, potential conflicts of interest, and constraints on the effectiveness of the KPK's authority following the legislative revision. The novelty of this study lies in its analysis of corruption prevention in Hajj governance by focusing on the KPK's preventive role after the revision of the KPK Law as part of broader efforts to realize good governance.